Can the Eight Hop Test Be Measured with Sensors? A Systematic Review - Pimenta, Luís; Garcia, Nuno M; Zdravevski, Eftim; CHorbev, Ivan; Trajkovikj, Vladimir; Albuquerque, Carlos; Lameski, Petre; Pires, Ivan Miguel (MDPI, 2022)
Rehabilitation aims to increase the independence and physical function after injury, surgery, or other trauma, so that patients can recover to their previous ability as much as possible. To be able to measure the degree of recovery and impact of the treatment, various functional performance tests are used. The Eight Hop Test is a hop exercise that is directly linked to the rehabilitation of people suffering from tendon and ligament injuries on the lower limb. This paper presents a systematic review on the use of sensors for measuring functional movements during the execution of the Eight Hop Test, focusing primarily on the use of sensors, related diseases, and different methods implemented. Firstly, an automated search was performed on the publication databases: PubMed, Springer, ACM, IEEE Xplore, MDPI, and Elsevier. Secondly, the publications related to the Eight-Hop Test and sensors were filtered according to several search criteria and 15 papers were finally selected to be analyzed in detail. Our analysis found that the Eight Hop Test measurements can be performed with motion, force, and imaging sensors.
Keywords: Eight Hop Test; systematic review; measurement; sensors; diseases